ANALISIS BERPIKIR KRITIS DALAM BUKU AJAR PENDIDIKAN AGAMA ISLAM KELAS XI - Shofiyah Hamidah; Nurhafiva Nurhafiva; Renzaidan Reizahran; Abdul Fadhil (Piwulang: Jurnal Pendidikan Agama Islam, 2023)
Critical thinking skills are abilities that are indispensable in facing life's challenges, especially in 21st century education. These skills can be trained and formed through education with learning activities so that they need to be included in the learning process using teaching material media. This research is focused on examining the contents of textbooks that apply aspects of critical thinking to Islamic Religious Education textbooks, the Independent Curriculum, published by the Ministry of Education and Culture. This study uses a qualitative research type with a descriptive research design, namely the description of the data is presented through the words contained in the Islamic Religious Education textbooks for class XI. The results of the study show that the textbooks for Class XI Islamic Religious Education published by the Ministry of Education and Culture as a whole contain aspects of critical thinking that are needed in today's 21st century education.